2012
DOI: 10.1002/anie.201203612
|View full text |Cite
|
Sign up to set email alerts
|

Bio‐Click Chemistry: Enzymatic Functionalization of PEGylated Capsules for Targeting Applications

Abstract: All sorted: The enzyme Sortase A was used to catalyze functionalization of PEGylated capsules with an activation-specific anti-platelet single-chain antibody (scFv). This enzymatic method allows fast, covalent, and site-directed functionalization of delivery vehicles under mild conditions. Activation-specific anti-platelet scFv-coated PEGylated capsules exhibited a high level of selective binding to thrombi, thus suggesting their potential for thrombosis therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 28 publications
(14 reference statements)
1
63
1
Order By: Relevance
“…[130] Further post-functionalization of the PEG surface with targeting ligands, e.g., RGD or scFv, was also achieved, providing multilayered capsules with targeting ability and enabling the capsules to be used as targeted drug carriers. [133,134] When preparing these types of multilayered capsules through LbL assembly, it has been shown that the assembly method used can substantially affect the resulting particles; therefore particles with tailored properties (but composed of the same materials) can be engineered through judicious choice of the assembly technology. [150] Additionally, PEG hydrogel particles with controllable size and tunable elasticity can be engineered using a MS templating method.…”
Section: Reducing Protein Adsorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…[130] Further post-functionalization of the PEG surface with targeting ligands, e.g., RGD or scFv, was also achieved, providing multilayered capsules with targeting ability and enabling the capsules to be used as targeted drug carriers. [133,134] When preparing these types of multilayered capsules through LbL assembly, it has been shown that the assembly method used can substantially affect the resulting particles; therefore particles with tailored properties (but composed of the same materials) can be engineered through judicious choice of the assembly technology. [150] Additionally, PEG hydrogel particles with controllable size and tunable elasticity can be engineered using a MS templating method.…”
Section: Reducing Protein Adsorptionmentioning
confidence: 99%
“…[59] This approach has been reported as an efficient method for attaching different targeting ligands, including Man, scFv, Tf, and polypeptides. [59,133,134,158] However, PEG itself could affect the efficiency of conjugating the ligand to the particle. Bargheer et al reported that higher PEGylation of iron oxide NPs resulted in diminished binding of Tf onto PEGylated particle surfaces.…”
Section: Wwwadvancedsciencenewscom Wwwadvhealthmatdementioning
confidence: 99%
“…Degradable therapeutic carriers must be modified with components which undergo partial or complete fragmentation under physiological conditions, allowing for carrier breakdown and release. Typical biodegradable polymers include synthetic polymers such as aliphatic polyesters, polycaprolactones, poly(ester amide)s, polyurethanes [4], and natural polymers such as DNA, polysaccharides, or polypeptides [5].…”
Section: Introductionmentioning
confidence: 99%
“…[6] The versatility of SML has been demonstrated previously, [7] but it has not been exploited to install a polymerization initiator at a defined site on a protein. The sortase A (SrtA) transpeptidase from S taphylococcus aureus recognizes the penta-peptide sequence “LPXTG” (lysine-proline-X-threonineglycine, where “X” is any standard amino acid residue) embedded in or terminally attached to a protein or peptide, and its cysteine (C) nucleophilically attacks the amide bond between threonine and glycine within the recognition sequence, generating a relatively long-lived enzyme-thioacyl intermediate.…”
Section: Introductionmentioning
confidence: 99%
“…The sortase A (SrtA) transpeptidase from S taphylococcus aureus recognizes the penta-peptide sequence “LPXTG” (lysine-proline-X-threonineglycine, where “X” is any standard amino acid residue) embedded in or terminally attached to a protein or peptide, and its cysteine (C) nucleophilically attacks the amide bond between threonine and glycine within the recognition sequence, generating a relatively long-lived enzyme-thioacyl intermediate. [6a] To complete transpeptidation, a second (bio)molecule with an N-terminal nucleophilic group, typically an oligoglycine motif, attacks the intermediate, displacing SrtA and joining the two molecules via a native peptide bond. [6a] …”
Section: Introductionmentioning
confidence: 99%